Key engineering materials VIII : the 8th International Conference on Key Engineering Materials (ICKEM 2018) - Korsunsky, Alexander M.; Makabe, Chobin; Wang, Emma (Trans Tech Publications Ltd., 2018)
We are very pleased to introduce the results of the 8th International Conference on Key Engineering Materials (8th ICKEM 2018). The conference was held in Osaka, Japan during March 16-18, 2018 and focused on research in the area of polymers and composites, nanomaterials and biomaterials, functional materials, materials in electronic engineering, surface engineering and coatings, electrochemistry; environmental and chemical engineering, alloys, steel, technologies of machining and metal recovery, materials mechanics and structural mechanics, building materials. Polymers, composites, nanomaterials, biomaterials, functional materials, materials for electronic engineering, surfaces, coatings, electrochemistry, environmental engineering, chemical engineering, alloys, steel, machining technologies, metal recovery, materials mechanics, structural mechanics, building materials, materials science.